EKSEKUSI JAMINAN FIDUSIA BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 2/PUU-XIX/2021 - Roma Borunami Olivia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The Constitutional Court has provided an interpretation of the provisions regarding the execution of fiduciary guarantees. Creditors have a legal right to carry out the execution of their fiduciary collateral object provided that there is an agreement on breach of contract (default) and the debtor's voluntary principle to surrender the fiduciary collateral object to the creditor. If these conditions are not fulfilled, the creditor must apply for execution to the court. This legal principle has been considered by some parties as not providing certainty and legal protection for good-faith fiduciary guarantee recipients. This article will discuss the process of executing fiduciary collateral objects, both in cases where there is an agreement on breach of contract and the debtor is willing to surrender the collateral object, and in cases where there is no such agreement and the debtor is not willing to surrender the collateral object.